Effect of Dynamic Load on Fiberglass and Coir-Based Hybrid Composite Stiffness - Mastariyanto Perdana (Jurnal Teknik Mesin, 2016)
The composites made from natural fibers have been widely used in the engineering field because the natural fiber-based composites have lightweight nature, relatively strong and environmentally friendly. The use the synthetic fiber-based composites reduced to obtain the environmentally friendly composites. In this study, the use synthetic fibers (fiberglass) reduced by adding coconut fiber (coir) on the composite mix. Composites in this study using the volume fraction of hybrid fiber 12% fiberglass and 18% coir. The volume fraction of fibers and epoxy hybrid is 30:70. This study aims to determine changes in stiffness of the hybrid composites due to dynamic loads. Hybrid composite loaded by 500, 1000, 1500, and 2000 cycles of the dynamic load. The test results show degradation of the rigidity of the hybrid composite. The stiffness decrease like presented by the ratio of E/Eo. The number of cycles of the dynamic load causes a decrease in stiffness hybrid composites. The stiffness of hybrid composites decrease because of dynamic load treatment reaches 30%.